First Report of blaIMP–4 and blaSRT–2 Coproducing Serratia marcescens Clinical Isolate in China - Huang, Xiangning; Shen, Siquan; Shi, Qingyu; Ding, Li; Wu, Shi; Han, Renru; Zhou, Xun; Yu, Hua; Hu, Fupin (Frontiers in Microbiology, 2021)
Carbapenem-resistant Enterobacterales (CRE) has become a major therapeutic concern in clinical settings, and carbapenemase genes have been widely reported in various bacteria. In Serratia marcescens, class A group carbapenemases including SME and KPC were mostly identified. However, there are few reports of metallo-β-lactamase-producing S. marcescens. Here, we isolated a carbapenem-resistant S. marcescens (S378) from a patient with asymptomatic urinary tract infection which was then identified as an IMP-4-producing S. marcescens at a tertiary hospital in Sichuan Province in southwest of China. The species were identified using MALDI-TOF MS, and carbapenemase-encoding genes were detected using PCR and DNA sequencing. The results of antimicrobial susceptibility testing by broth microdilution method indicated that the isolate S. marcescens S378 was resistant to meropenem (MIC = 32 μg/ml) and imipenem (MIC = 64 μg/ml) and intermediate to aztreonam (MIC = 8 μg/ml). The complete genomic sequence of S. marcescens was identified using Illumina (Illumina, San Diego, CA, United States) short-read sequencing (150 bp paired-end reads); five resistance genes had been identified, including blaIMP–4, blaSRT–2, aac(6′)-Ic, qnrS1, and tet(41). Conjugation experiments indicated that the blaIMP–4-carrying plasmid pS378P was conjugative. Complete sequence analysis of the plasmid pS378P bearing blaIMP–4 revealed that it was a 48,780-bp IncN-type plasmid with an average GC content of 50% and was nearly identical to pP378-IMP (99% nucleotide identity and query coverage).